2014
DOI: 10.2519/jospt.2014.5294
|View full text |Cite
|
Sign up to set email alerts
|

Early Ankle Movement Versus Immobilization in the Postoperative Management of Ankle Fracture in Adults: A Systematic Review and Meta-analysis

Abstract: T he incidence of ankle fracture is 71 per 100 000 person-years. There are age and sex differences, with peak incidence in younger men (between 15 and 29 years of age), whereas in women the incidence peaks at over 50 years of age. 38 Ankle fracture is caused by injury during physical activity and sport, and, in older people, osteoporosis is an important contributor. 19 Projections from Scandinavia suggest that the number of ankle fractures will increase 3-fold between 2006 and 2030, driven by the aging populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 33 publications
4
38
1
5
Order By: Relevance
“…[8] Hence, that is why the endpoint of the present study is limited to the 3rd month after surgery. In reality, some studies [16–18] previously reported have supported the point of view that early exercise or mobilization can reduce the risk of developing lower limb DVT after an operation. And early mobilization in patients with acute deep vein thrombosis does not increase the risk of a symptomatic pulmonary embolism.…”
Section: Discussionmentioning
confidence: 87%
“…[8] Hence, that is why the endpoint of the present study is limited to the 3rd month after surgery. In reality, some studies [16–18] previously reported have supported the point of view that early exercise or mobilization can reduce the risk of developing lower limb DVT after an operation. And early mobilization in patients with acute deep vein thrombosis does not increase the risk of a symptomatic pulmonary embolism.…”
Section: Discussionmentioning
confidence: 87%
“…The OMAS is one of the most commonly used outcome measures in ankle fracture research, 23,110 but has been criticised for methodological shortcomings in its development. 111 We found no published minimal clinically important differences for the OMAS and, therefore, had to develop the sample size drawing on wider literature and in consultation with clinical experts.…”
Section: Internal Validity and Methodologymentioning
confidence: 99%
“…After a fracture of the lower extremity, the period of immobility of the affected limb and the time of hospitalization of these patients may be factors capable of negatively influencing the body composition and the physical-functional aspects of the patients. Due to the need for postoperative medical follow-up and long periods of bed restriction in the hospital phase, it can cause muscular and bone hypotrophy, ligament and capsular retraction, joint stiffness and circulatory changes [17,18]. Even after years of hospital discharge, the patient may present negative physical-functional consequences, since there may be a delay in joining a rehabilitation program due to the difficulty of access to the public health system or the lack of effectiveness of the treatment [19,20].…”
Section: Introductionmentioning
confidence: 99%